Producción del fonema /s/ en una muestra de niños hablantes del español de Chile: adquisición de los aspectos dialectales - Vivar, Pilar Vivar (2020)
The alveolar fricative consonant /s/ in plosive position (middle and end of the word) was studied in a sample composed by 161 speakers of ChileanSpanish, divided in four age groups from 2;0 up to 3;11. The main purpose of the study was to consider this segment from a dialectal perspective, in order to understand at what point in its acquisition children start to use this sound’s variants, i.e., [h] and [Ø]. Results were analyzed according to age and socioeconomic status variables.